2022
DOI: 10.1111/bjd.21783
|View full text |Cite
|
Sign up to set email alerts
|

Insights into male androgenetic alopecia using comparative transcriptome profiling: hypoxia-inducible factor-1 and Wnt/β-catenin signalling pathways

Abstract: BackgroundThe key pathophysiological changes in androgenetic alopecia (AGA) are limited to hair follicles (HFs) in frontal and vertex regions, sparing the occipital region. Objectives To identify biological differences among HF subpopulations. Methods Paired vertex and occipital HFs from 10 male donors with AGA were collected for RNA sequencing assay. Furthermore, HF and cell experiments were conducted on the identified key genes to reveal their roles in AGA. Results Transcriptome profiles revealed that 506 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Hence, our findings regarding sebocyte apoptosis, IP collapse, local inflammation, and pain-related pathways require confirmation in additional donors and subsequent studies. Finally, the range of biomarkers studied should be greatly expanded, including wound healing/trauma-associated products of genes that have recently been reported to be associated with androgenetic alopecia [169] or that are known to regulate wounding-induced HF neogenesis in adult mice [170]; moreover, indicators of long-term HF and skin wounding memory [171], especially after repetitive epilation, could be studied. In addition, the impact of epilation on human HF innervation [172], neuroendocrine signalling [173][174][175], and the human HF microbiome [165,176] remains to be investigated, and our hypothesis-driven protein−/celllevel data should be complemented with hypothesis-free transcriptomic data at various time points post-epilation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our findings regarding sebocyte apoptosis, IP collapse, local inflammation, and pain-related pathways require confirmation in additional donors and subsequent studies. Finally, the range of biomarkers studied should be greatly expanded, including wound healing/trauma-associated products of genes that have recently been reported to be associated with androgenetic alopecia [169] or that are known to regulate wounding-induced HF neogenesis in adult mice [170]; moreover, indicators of long-term HF and skin wounding memory [171], especially after repetitive epilation, could be studied. In addition, the impact of epilation on human HF innervation [172], neuroendocrine signalling [173][174][175], and the human HF microbiome [165,176] remains to be investigated, and our hypothesis-driven protein−/celllevel data should be complemented with hypothesis-free transcriptomic data at various time points post-epilation.…”
Section: Discussionmentioning
confidence: 99%
“…While lower numbers of hair follicles were used per sample, it is unclear whether this, the storage conditions or the extraction protocol was the reason for the poorer quality of RNA reported. Many such studies aim to evaluate gene expression to better understand hair growth in order to provide potential targets for the treatment of human hair loss and other skin conditions (23,24). An equine study by Naboulsi et al, (2022), found that keratin-related genes were more plentiful in hair follicle samples than in skin biopsies, making HF an excellent tissue for functional studies on colouration, shape, and growth of hair as these characteristics can be attenuated in skin biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Assays using HFs obtained through plucking, follicular unit extraction (FUE), and skin biopsies have been performed. Through a comprehensive literature search, we found 9 studies involving human HGs [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. In most studies (67%), the complete HF was used to obtain mRNA samples.…”
Section: Transcription Profiling Studies Of Agamentioning
confidence: 99%